CONTROL AND GRADE COMPETENCE FUTURE TEACHERS OF MATHEMATICS - Tatochenko В.І.; Shypko А.Л. (Journal of Information Technologies in Education (ITE), 2016)
The article is devoted to the theoretical study of the problem of formation of control and grade competence of the students - future teachers of mathematics while studying special subjects.The essence of such notions as competence, professional competence, methodical competence,control and grade competence of the Mathematics teacher are differentiated. The following subjects are described: the goal orientation, the resource potential of the educational process and its objectives: to form the system of necessary methodological knowledge and skills, the system of pedagogical values that form the willingness for the control and grade activities at all stages of learning, which are derived from the objectives and available resources: content and training tools. Identified approaches (system, personal active, competent, technological, communicative active) and the dominant principles necessary to form control and grade competence of the future Mathematics teachers (consistency, functionality of knowledge and skills, personal orientation,assessment of academic achievements of the student in accordance with the quality of Mathematics education). Contradictions are described and pedagogical conditions to provide this process are justified. The structure of the control and grade competence is characterized,including the motivation, professional skills, acquired knowledge and skills, activities of the subjects of the study; and its following components: motivational, cognitive, activity, reflective.The following stages of the formation of the control and grade competence are defined:motivational, informative, technological, assessment and effective. To form the control and grade competence of the students - future Mathematics teachers the technology of construction and solving of methodological situational tasks is suggested. The following criteria are identified:motivational, essential, activity; the following indicators are stated: motivation, knowledge, skills,results of activity; the following levels of control and grade competence are described: beginner,intermediate, adequate, advanced. The model of formation of control and grade competence of the future Mathematics teachers while teaching professional disciplines is created, the structural units of which are objective normative, methodological, essential, technological, and assessment and effective.